2023
DOI: 10.1111/add.16261
|View full text |Cite
|
Sign up to set email alerts
|

Systematic assessment of non‐medical use of prescription drugs using doctor‐shopping indicators: A nation‐wide, repeated cross‐sectional study

Abstract: AimsThe aim of this study was to present the first nation‐wide, systematic, repeated assessment of doctor‐shopping (i.e. visiting multiple physicians to be prescribed the same drug) during 10 years for more than 200 psychoactive prescription drugs in the 67 million inhabitants in France.DesignThis was a nation‐wide, repeated cross‐sectional study.Setting and ParticipantsData are from the French National Health Data System in 2010, 2015 and 2019 for 214 psychoactive prescription drugs (i.e. anaesthetics, analge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…The doctor shopping analysis performed in our study has shown that this does not seem to be a cause for concern in ARSLVT. In France the scenario is different, with several studies (Ponté et al, 2018 ; Pradel et al, 2010 ; Soeiro et al, 2023 ) pointing to higher DSI, and for more PMed, than in ARSLVT. In our results, although the DSQ for BZD (14.0 DDD/100,000 inhabitants/day) was almost 2-fold higher than for OA (corrected DSQ = 8.6 DDD/100,000 inhabitants/day), their doctor shopping indicator (0.3%) was one fifth that of OA (1.5%).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The doctor shopping analysis performed in our study has shown that this does not seem to be a cause for concern in ARSLVT. In France the scenario is different, with several studies (Ponté et al, 2018 ; Pradel et al, 2010 ; Soeiro et al, 2023 ) pointing to higher DSI, and for more PMed, than in ARSLVT. In our results, although the DSQ for BZD (14.0 DDD/100,000 inhabitants/day) was almost 2-fold higher than for OA (corrected DSQ = 8.6 DDD/100,000 inhabitants/day), their doctor shopping indicator (0.3%) was one fifth that of OA (1.5%).…”
Section: Discussionmentioning
confidence: 97%
“…excessive use) of a given medicine. Doctor shopping parameters were calculated and analysed according to the methodology described by several authors (Frauger et al, 2011 , 2016 ; Micallef et al, 2015 ; Ponté et al, 2018 ; Pradel et al, 2004 , 2009 , 2010 ; Soeiro et al, 2023 ), both at INN and at therapeutic group level. A detailed description of the method, that considers the number of overlaps of prescriptions of a given medicine or therapeutic group issued by different prescribers, is provided in Supplemental Material 1 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation